Brief soaking at above‐gelatinization temperature reduces inorganic arsenic in cooked rice. Issue 1 (29th June 2020) - Chen, Guoying; Lai, Bunhong; Chen, Tuanwei; Lin, Hetong; Mao, Xuefei
Abstract: Background and objectives: Rice contains an order of magnitude higher inorganic arsenic (iAs), a class 1 non‐threshold carcinogen, than other terrestrial crops. To reduce iAs in cooked rice, several methods have been proposed such as washing until clear, cooking with high water‐to‐rice ratio (W/R) then discarding excess water, or continuously percolating near‐boiling water. The traditional method practiced by 1.6 billion East Asians, washing and cooking with low W/R until dry, removes only a small percentage of iAs. A new approach was investigated to reduce iAs in cooked rice. Findings: Brief (10 min) soaking (W/R 10) at above gelatinization temperature (80°C) reduced iAs in rice by up to 48.4%. A soaking protocol was developed for public use that on average reduced 39.5 ± 6.6% ( n = 12) iAs in non‐waxy white rice. Conclusions: Brief above‐gelatinization‐temperature soaking effectively reduces iAs in cooked white rice. Significance and novelty: Above‐gelatinization‐temperature soaking was applied for the first time to cut iAs in cooked rice; thereby chronic iAs exposure and cancer risk can be reduced for rice consumers. Abstract : Carcinogenic inorganic arsenic in non‐waxy white rice was reduced by 39.5±6.6% (n=12) by 10 min soaking in 10x water at above‐gelatinization‐temperature (80 °C), discarding soaking water, then cooking by traditional East‐Asian cook‐until‐dry method.